[ARIA 2019: An Integrated Care Pathway for Allergic Rhinitis in Portugal] - Fonseca, J (2020)
The Allergic Rhinitis and Its Impact on Asthma (ARIA) initiative started more than 20 years ago and has developed and disseminated evidence-based guidelines and projects in the field of allergic rhinitis. This initiative is currently focused on providing patient-centred guidelines that contribute to an integrated care pathway between the various levels of care and take advantage of digital solutions, and the introduction of integrated care pathways in clinical practice has been recommended. In this article we describe the adaptation for Portugal of the ARIA Integrated Care Pathways document. After a brief review of the epidemiology and impact of allergic rhinitis in Portugal and the activities carried out in Portugal within the ARIA initiative, we describe the broad knowledge base used for the development of recommendations for the pharmacological treatment of allergic rhinitis, and these recommendations are based on the GRADE methodology, real world evidence acquired by mobile technology (mHealth) and resulting from allergenic exposure chamber studies. What follows is a summary of integrated care pathways for allergen immunotherapy produced in 2019. Allergen immunotherapy is considered an example of precision medicine where the use of mHealth technologies will improve stratification for patient selection and response monitoring. These recommendations were considered as best practices of integrated patient-centred care supported by digital systems from Directorate General for Health and Food Safety of the European Union (DG Santé) and represent the ARIA Phase 4 Change Management strategy.